Murder at an Irish wedding - O'Connor, Carlene (O'Connor, Carlene. Irish village mystery, 2017)
Any wedding is a big deal in the County Cork village of Kilbane, but with a local lad marrying a famous fashion model at Kilbane Castle, there<U+2019>s no talk of anything but the upcoming nuptials. Siobhán O<U+2019>Sullivan and her five siblings have their plates full catering the three-day affair from their bistro. But the celebratory mood suddenly turns sober when the best man is found murdered in the woods. For Siobhán, the tragic turn is more than grist for the gossip mill. Her beau, Macdara Flannery, is the prime suspect<U+2014>and she intends to clear his name. Now, like the bride walking down the aisle, Siobhán needs to watch her step. For as she gets closer to unveiling the truth, the murderer is planning a very chilly reception for her.